CDMA-Based UHF-RFID System with Semi-Passive UHF Transponders - Löffler, Andreas; Schuh, Fabian; Altmann, Ingo (2011)
UnivIS-Import:2015-03-09:Pub.2011.tech.IE.komele.cdmaba

Statistische Analyse und Auswertung von MIMO-Funkkanalmessungen - Schuh, Fabian (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2010)

The generalized frequency-domain adaptive filtering algorithm implemented on a GPU for large-scale multichannel acoustic echo cancellation - Schneider, Martin; Schuh, Fabian; Kellermann, Walter (ITG Symposium on Speech Communication, 2012)
For multichannel reproduction systems a trend towards increasing numbers of reproduction channels can be observed. For the use of such systems in communication scenarios, acoustic echo cancellation (AEC) is necessary, whose computational complexity scales at least linearly with the number of reproduction channels and implies a tremendous computational effort. Powerful graphics processing units (GPUs) appear to be a suitable implementation platform for such a scenario. However, inexpensive consumer-market GPUs are not designed for real-time adaptive audio processing with low-latency. In this paper we present an implementation of the Generalized Frequency-Domain Adaptive Filtering (GFDAF) algorithm on popular GPUs. Details on the parallelization of the algorithm are given and the performance of the implementation is evaluated for single precision and for double precision computation